1956
DOI: 10.1017/s0022172400044570
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of tetanus toxin by brain tissue

Abstract: The potency of tetanus toxin as measured by combining power is markedly reduced by mixing with fresh or dried preparations of rabbit brain, and by dried horse brain. A number of other bacterial toxins are not so affected.Tissues other than brain were not found to have this specific effect.The state of division of the tissue, the time over which adsorption takes place, and the relative proportions of adsorbate and adsorbent affect the quantity of toxin removed. When the quantity of adsorbent and the volume of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1959
1959
1977
1977

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…van Heyningen protein. As is known from previous work (Fulthorpe, 1956; van Heyningen, 1959), and as can be seen in Table 1 and in Fig. 4, the amount of tetanus toxin adsorbed increased with increasing concentration of toxin.…”
Section: -2supporting
confidence: 80%
“…van Heyningen protein. As is known from previous work (Fulthorpe, 1956; van Heyningen, 1959), and as can be seen in Table 1 and in Fig. 4, the amount of tetanus toxin adsorbed increased with increasing concentration of toxin.…”
Section: -2supporting
confidence: 80%
“…2, and the advantage of a test dose that is two-thirds of a given amount of toxin, is shown by the observation that although the weight of the Receptor Unit of a certain preparation of protagon was 0.58 mg. when measured against 30 L + doses of toxin + 10 units antitoxin, it was 6.0 mg. when measured against 20 L + alone. Table 5 shows that the weight of the Receptor Unit decreased with increasing toxin concentration, as might be expected from Fulthorpe's (1956) observation that the higher the toxin concentration the greater the amount of toxin adsorbed, However, the greater consumption of toxin and antitoxin did not justify carrying out the assay a t concentrations of toxin above 30 L + /ml. Table 6 shows that this method of assay gave satisfactorily reproducible results.…”
Section: Effect Of Receptor Concentration On Adsorption Of Toxinmentioning
confidence: 73%
“…It was realized then that with a test dose of 10 LD50 the concentration of toxin used, in terms of weight of toxic protein/unit volume, was extremely low, of the order of 0.002 pg./ml. Fulthorpe (1956) showed that the fixation of tetanus toxin by brain follows the usual laws of adsorption, i.e. the greater the concentration of toxin the greater the amount adsorbed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metchnikoff (1898) was unable to demonstrate the neutralization of tetanus toxin by bird brain tissue, but recently van Heyningen (1959a) found chicken brain to be as active as mammalian brain tissue in the absorption of tetanus toxin. The reaction between brain tissue and tetanus toxin is a reversible absorption process (Fulthorpe, 1956), the amount of toxin absorbed depending on the concentration of toxin. Metchnikoff may well have failed to demonstrate absorption of the toxin by bird brain because he used too low a concentration of toxin.…”
Section: Discussionmentioning
confidence: 99%